Coexistence of prostate cancer and disseminated hepatocellular carcinoma – a case report - Szydłowska-Pazera, Katarzyna; Potemski, Piotr; Tomczyk, Dorota; Kubiak, Robert; Jaworski, Tomasz; Płużańska, Anna (Contemporary Oncology/Współczesna Onkologia, 2006)
A case of a 64-year old male with multiple bone metastases is presented. Because of elevated serum PSA level an oligobiopsy of the prostate was performed and a single focus of grade 1 prostatic cancer was found. The patient was treated with flutamide and gosereline. However, as the bone metastases progressed a surgical biopsy of the sternum was performed and a diagnosis of disseminated hepatocellular carcinoma was established. AFP serum level was normal. CT scan revealed a heterogeneous liver without focal lesions. A fine needle biopsy of the liver confirmed the diagnosis. The patient was treated ineffectively with palliative chemotherapy.